The Effect of Moringa Leaf Decoction and Moderate Exercise on Hemodynamic Changes in Hypertensive Patients at Namo Rambe Public Health Center, Deli Serdang Regency - Adinda Nazwhanda Alvito Sitorus; Gusbakti Rusip; Sri Wahyuni Nasution (Publikasi Indonesia, 2025)
Hypertension is a global health problem that requires complementary non-pharmacological interventions, given the high risk of complications and treatment costs. Moringa (Moringa oleifera) leaves are known to contain quercetin, which has diuretic and antioxidant properties, while moderate exercise is proven to improve endothelial function. This study aims to prove the effect of the combination of moringa leaf decoction and moderate exercise on hemodynamic changes (blood pressure) in hypertension patients. This study used a quasi-experimental design with a one group pretest-posttest approach. The research sample consisted of hypertension patients in the working area of Namo Rambe Primary Health Care, Deli Serdang Regency. The combined intervention (administration of moringa leaf decoction and moderate exercise) was carried out for 21 days. Systolic and diastolic blood pressure measurements were taken before (pretest) and after (posttest) the intervention. Data were analyzed using the Paired Sample t-Test. The analysis results showed that the average systolic blood pressure decreased significantly from 168.00 mmHg (pretest) to 121.87 mmHg (posttest). Similarly, diastolic blood pressure decreased from an average of 97.81 mmHg (pretest) to 77.13 mmHg (posttest). The Paired Sample t-Test results showed a significance value (p-value) of 0.000 (p < 0.05) for both systolic and diastolic blood pressure. There is a highly significant effect of the combined administration of moringa leaf decoction and moderate exercise on hemodynamic changes in hypertension patients. This intervention is effective in lowering blood pressure and is recommended as a safe and affordable complementary therapy in the management of hypertension